Detection and Distribution of V1016I(kdr) Mutation in the Voltage-Gated Sodium Channel Gene in Aedes aegypti (Diptera: Culicidae) Populations From Sergipe State, Northeast Brazil - Dolabella, S. S.; Santos, R. L. C.; Silva, M. C. N.; Steffler, L. M.; Ribolla, P. E. M. [UNESP]; Cavalcanti, S. C. H.; Jain, S.; Martins, A. J. (Oxford Univ Press Inc, 2016)
Aedes aegypti (L.) resistance to pyrethroids was recorded in Brazil few years after its introduction as the adulticide in the National Dengue Control Program campaigns. Altered susceptibility to pyrethroids had been reported in the state of Sergipe, northeast Brazil, through biological assays, even before its use against Ae. aegypti in the state. Metabolic and target-site resistance mechanisms were also revealed in samples from Aracaju, the capital of Sergipe. Herein, we investigated the presence and distribution of the kdr mutation V1016I(kdr) in Ae. aegypti populations from different municipalities of the state. Aedes aegypti eggs were collected from seven municipalities located in areas showing different climatic types and infestation levels. Approximately 20 Ae. aegypti females from each municipality (total of 135 subjects) were individually submitted to allele-specific polymerase chain reaction (AS-PCR) for the 1016 site of the voltage-gated sodium channel (NaV). The V1016I(kdr) mutation was found in subjects from all the municipalities under study with a high frequency of heterozygotes in several locations. Homozygous recessive subjects (resistant kdr genotype) were found only in one municipality. The results suggest a wide distribution of the V1016I(kdr) mutation in the northeast Brazil, which indicates urgent need for monitoring the effectiveness of the pyrethroids currently used for vector control.
Keywords: Aedes aegypti; kdr mutation; pyrethroid resistance; sodium channel